Eschenmoser Coupling Reaction and Reactivity of Hydrazinecarbothioamides in the Synthesis of Benzindazole and Naphthothiazole Derivatives - Hassan, Alaa A.; Mohamed, Nasr K.; El-Shaieb, Kamal M. A.; Tawfeek, Hendawy N.; Bräse, Stefan; Nieger, Martin (Synthesis, 2017)
N-Unsubstituted and N-substituted 2-phenylhydrazinecarbothioamides react with 2,3-dichloro-1,4-naphthoquinone to give a series of unprecedented 3-amino- and 3-(alkylamino)-1-phenyl-1H-benzo[f]indazole-4,9-diones in good yields. On the other hand, the reaction of N-substituted 2-tosylhydrazinecarbothioamides with 2,3-dichloro-1,4-naphthoquinone afforded (Z)-N-[3-(tosylamino)-4,9-dioxo-4,9-dihydronaphtho[2,3-d]thiazol-2(3H)-ylidene]-substituted aminium chlorides and (Z)-N-[(2-substituted imino)-4,9-dioxo-4,9-dihydronaphtho[2,3-d]thiazol-3(2H)-yl]-4-toluenesulfonamide hydrates.
Keywords: hydrazinecarbothioamides; 2,3-dichloro-1,4-naphthoquinone; benzo[f]indazole-4,9-diones; naphtho[2,3-d]thiazoles; Eschenmoser reaction